Initiation of adjuvant therapy following surgical resection of pancreatic ductal adenocarcinoma (PDAC): Are patients from rural, remote areas disadvantaged?. Issue 8 (14th May 2018) - Bertens, Kimberly A.; Massman, John D.; Helton, Scott; Garbus, Samuel; Mandelson, Margaret M.; Lin, Bruce; Picozzi, Vincent J.; Biehl, Thomas; Alseidi, Adnan A.; Rocha, Flavio G.
Abstract : Background and Objectives: Although race and socioeconomic status have been shown to affect outcomes in pancreatic ductal adenocarcinoma (PDAC), the impact of rural residence on the delivery of adjuvant therapy (AT) has not been studied. Methods: Patients with resected PDAC were identified using the National Cancer Database (NCDB). Individuals were classified as living in a metro area, urban/rural adjacent to a metro area (URA), and urban/rural remote (URR) area. Multivariate logistic regression was used to assess geographic inhabitance as a predictor of receiving AT. Results: A total of 32 521 individuals who underwent pancreatectomy for PDAC were identified. Univariate analysis demonstrated individuals in URR areas were less likely to receive adjuvant chemotherapy (ACT) than those living in URA or metro areas (55.3% vs 55.6% vs 58.8%, P = 0.011). However on multivariate analysis URR inhabitance was no longer a predictor of ACT (OR = 0.911 P = 0.125) or ART (OR = 0.953 P = 0.462). Cox proportional hazard modeling demonstrated URR inhabitance remained independently associated with poor OS (HR 1.076; 95% CI [1.008, 1.149], P < 0.029). Conclusions: URR inhabitance does not impact access to AT, however it is independently associated with a decreased OS. Attention must be focused on optimizing oncologic care to patients with disparate access to healthcare.